Job creation and the intra-distribution dynamics of the firm size distribution - Peter Huber; Harald Oberhofer; Michael Pfaffermayr (University of Salzburg, Department of Social Sciences and Economics, 2012)
Based on a three equations model for initial firm size, survival and firm growth we estimate firm-specific transition probabilities between size classes of the firm size distribution. This allows to analyze counterfactual scenarios that assess the impact of changes in exogenous variables on the intra-distribution dynamics of the firm size distribution. We find that a counterfactual decrease in average firm age increases the exit hazard of young firms, and at the same time reduces the probability to observe high growth firms. An increase in the industry-wide entry rate and an increase in market growth, by contrast, havw virtually no impact on the intra-distribution dynamics of the firm size distribution. Finally, a larger birth size increases the probability for the youngest and smallest firms to be fast growing ones.
Keywords: C24; D22; L11; L25; L26; M13; 330; Firm growth; survival; entry size; high growth firms; counterfactual scenario analysis; sample selection